The cardiovascular effects of central hydrogen sulfide are related to KATP channels activation - Liu, W. Q; Chai, C; Li, X. Y; Yuan, W. J; Wang, W. Z; Lu, Y (Physiological research, 2011)
Hydrogen sulfide (H2S), an endogenous “gasotransmitter”, exists in the central nervous system. However, the central cardiovascular effects of endogenous H2S are not fully determined. The present study was designed to investigate the central cardiovascular effects and its possible mechanism in anesthetized rats. Intracerebroventricular (icv) injection of NaHS (0.17~17 μg) produced a significant and dose-dependent decrease in blood pressure (BP) and heart rate (HR) (P<0.05) compared to control. The higher dose of NaHS (17 μg, n=6) decreased BP and HR quickly of rats and 2 of them died of respiratory paralyse. Icv injection of the cystathionine betasynthetase (CBS) activator s-adenosyl-L-methionine (SAM, 26 μg) also produced a significant hypotension and bradycardia, which were similar to the results of icv injection of NaHS. Furthermore, the hypotension and bradycardia induced by icv NaHS were effectively attenuated by pretreatment with the KATP channel blocker glibenclamide but not with the CBS inhibitor hydroxylamine. The present study suggests that icv injection of NaHS produces hypotension and bradycardia, which is dependent on the KATP channel activation.
Keywords: KATP kanály; KATP Channels; Blood Pressure; Ion Channel Gating; Heart Rate; zvířata; sulfan; Rats; srdeční frekvence; potkani Sprague-Dawley; mužské pohlaví; Heart; srdce; Brain; gating iontového kanálu; mozek; krysa rodu Rattus; Hypotension; Animals; bradykardie; Male; Bradycardia; hypotenze; Hydrogen Sulfide; Rats, Sprague-Dawley; krevní tlak